Exchange-split multiple Rydberg series of excitons in anisotropic quasi two-dimensional ReS2. (1st October 2022) - Kapuściński, P; Dzian, J; Slobodeniuk, A O; Rodríguez-Fernández, C; Jadczak, J; Bryja, L; Faugeras, C; Basko, D M; Potemski, M
Abstract: We perform a polarization-resolved magnetoluminescence study of excitons in ReS2 . We observe that two linearly polarized Rydberg series of excitons are accompanied by two other Rydberg series of dark excitons, brightened by an in-plane magnetic field. All series extrapolate to the same single-electron bandgap, indicating that the observed excitons originate either from the same valley or from two valleys related by the inversion symmetry, and are split by exchange interaction. To interpret our observations of the magnetic brightening, we have to assume the dominant spin–orbit coupling to be Ising-like, which hints at an approximate symmetry of the electronic states in ReS2 which is higher than the crystal symmetry C i .